JURIDICAL ANALYSIS OF ELECTRICITY-RELATED CRIMES COMMITTED BY BITCOIN MINING EMPLOYEES IN THE DECISION OF THE MEDAN DISTRICT COURT NUMBER 497/PID.SUS/2024/PN MDN - Putra Junico; Muhammad Ridwan Lubis (Jurnal Ilmu Hukum dan Keadilan, 2026)
Based on the research results, it shows that there are no specific legal regulations governing the crime of electricity theft in Indonesia, particularly in the context of Bitcoin mining activities. However, if the electricity is used illegally, Article 362 of the Criminal Code concerning Theft or Article 51 paragraph (3) of Law No. 30 of 2009 concerning Electricity can be used. The elements of the crime of electricity theft applied to the theft case in Decision Number 497/Pid.Sus/2024/PN Mdn are appropriate and legally based, namely, proven by the existence of witness testimony, documentary evidence, indicative evidence, and the defendant's testimony. Criminal liability for perpetrators of electricity theft in Decision Number 497 is a prison sentence of 5 years and 6 months and a fine of Rp1,000,000,000.00